2015
DOI: 10.1016/j.scitotenv.2014.04.089
|View full text |Cite
|
Sign up to set email alerts
|

Flow and sorption controls of groundwater arsenic in individual boreholes from bedrock aquifers in central Maine, USA

Abstract: To understand the hydrogeochemical processes regulating well water arsenic (As) evolution in fractured bedrock aquifers, three domestic wells with [As] up to 478 µg/L are investigated in central Maine. Geophysical logging reveals that fractures near the borehole bottom contribute 70–100% of flow. Borehole and fracture water samples from various depths show significant proportions of As (up to 69%) and Fe (93–99%) in particulates (>0.45 µm). These particulates and those settled after a 16-day batch experiment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 78 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…In addition, groundwater may flow in fractures that are totally isolated from each other. It is plausible that anoxic/suboxic zones may develop in such fractures, locally favouring the desorption of As(III) bound to Fe-oxides as has been suggested by Yang et al (2015). Whether a borehole intercepts a groundwater flow path very close to a mineralised zone is likely the main factor affecting whether or not elevated arsenic is present in the well.…”
Section: Arsenic and Lithologymentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, groundwater may flow in fractures that are totally isolated from each other. It is plausible that anoxic/suboxic zones may develop in such fractures, locally favouring the desorption of As(III) bound to Fe-oxides as has been suggested by Yang et al (2015). Whether a borehole intercepts a groundwater flow path very close to a mineralised zone is likely the main factor affecting whether or not elevated arsenic is present in the well.…”
Section: Arsenic and Lithologymentioning
confidence: 88%
“…The oxidation of such sulphide minerals when in contact with oxygen-containing groundwater and subsequent release of arsenic to solution can lead to considerably elevated groundwater arsenic concentrations (Verplanck et al, 2008;Walker et al, 2006;Yang et al, 2015). In general, depending on the redox conditions in the subsurface, arsenic should stay in solution in its reduced form As(III) if reducing conditions are prevalent, but should be tightly adsorbed to iron hydroxides if conditions are oxidising (Dixit & Hering, 2003).…”
Section: Hydrological and Geological Setting And Its Relevance To Elevated Arsenic Concentrationsmentioning
confidence: 99%
“…This suggests a more complex mechanism of As mobilization and is consistent with multiple As host minerals changing with progressive metamorphism where As-silicates are proposed as possible host minerals. Secondary Fe or Mn minerals in fractures likely contribute to As distribution in groundwater via pH-influenced desorption or reductive dissolution (Yang et al, this issue). Probably many of these phases are unstable, and also exist as some form of grain coatings but could be derived from the weathering of As-primary minerals in these metamorphic rocks.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the concentrations of As from all private wells (n=616) are less variable than those from public wells (n=629), suggesting that the frequency of regular monitoring recommended for private wells by government agencies is likely to be sufficient for most wells, with a caveat that water usage or pumping rates do not vary a great deal for individual households. This caveat is because studies, including Yang et al (this issue), found that total (un-filtered and acidified) As concentrations in well water varied considerably when the borehole was pumped over several hours, although the dissolved (filtered and acidified) As concentrations in well water varied little (Bottomley, 1984; Yang et al, this issue). Both studies suggest that As sorbed to Fe precipitates in a borehole can account for differences in total and dissolved well water As concentrations during pumping, with Yang et al (this issue) proposing a conceptual model invoking sorption control of As onto secondary Fe minerals along a groundwater flow path following an oxic-suboxic(-anoxic)-suboxic-oxic gradient from “recharge” to “discharge” into the borehole as a plausible mechanism.…”
Section: Risks From Arsenic In Private Well Water Of Northeast Unitmentioning
confidence: 99%